2020
DOI: 10.3389/fphys.2020.00615
|View full text |Cite
|
Sign up to set email alerts
|

Diazotroph Diversity Associated With Scleractinian Corals and Its Relationships With Environmental Variables in the South China Sea

Abstract: Coral reef ecosystems cannot operate normally without an effective nitrogen cycle. For oligotrophic coral reef areas, coral-associated diazotrophs are indispensable participants in the nitrogen cycle. However, the distribution of these diazotrophs and the correlation with the physical and chemical variables of the surrounding seawater remain unclear. To this end, 68 scleractinian coral colonies were sampled from 6 coral reef areas with different environmental variables in the South China Sea to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…S5 and S6 ). Given the prevalence of Cluster V nifH sequences across coral species, analyses of nifH diversity or gene copy number that do not differentiate between nifH clusters (e.g., [ 10 , 24 , 101 ]) could overestimate diazotrophic diversity and activity in coral. Moreover, taxa containing Cluster V chlorophyllide genes, such as Ostreobium , are known to bloom during coral bleaching events [ 86 ], which means that particular care must be exercised when analyzing nifH abundance in bleaching studies.…”
Section: Discussionmentioning
confidence: 99%
“…S5 and S6 ). Given the prevalence of Cluster V nifH sequences across coral species, analyses of nifH diversity or gene copy number that do not differentiate between nifH clusters (e.g., [ 10 , 24 , 101 ]) could overestimate diazotrophic diversity and activity in coral. Moreover, taxa containing Cluster V chlorophyllide genes, such as Ostreobium , are known to bloom during coral bleaching events [ 86 ], which means that particular care must be exercised when analyzing nifH abundance in bleaching studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also observed a mismatch with lower DDN assimilation rates in corals where genes involved in N 2 fixation were predicted (using PICRUSt2 ) to be enriched in comparison with other corals ( Lesser et al, 2019 ). Interestingly, Liang et al (2020) indicated that corals are not necessarily associated with diazotrophs for the acquisition of newly fixed nitrogen. They found for several coral species from the South China Sea that the nutrient availability in the reef water could completely meet the nitrogen demand of coral holobionts, even without biological N 2 fixation by coral-associated diazotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in N 2 fixation in coral holobionts may also be linked to changes in the coral-associated diazotrophic community. The composition of these communities is known to vary between coral species, environmental conditions and geographical location ( Lema et al, 2014b ; Zhang et al, 2016 ; Lesser et al, 2018 ; Liang et al, 2020 ). In particular, seasonal shifts of ammonium and nitrate in the surrounding seawater have been suggested to drive seasonal changes in diazotrophic communities associated with corals ( Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rich in biodiversity and productivity, coral reefs are found in oligotrophic waters in the tropics that are extremely scarce in nutrients (Fiore et al, 2010;Ceh et al, 2013;Rädecker et al, 2015;Pogoreutz, 2016). This strange phenomenon of being highly productive in nutrient wastelands represents the "Darwin Paradox" (Rädecker et al, 2015;Pogoreutz, 2016), largely successful due to the symbiotic interactions occurring within the coral holobiont (Wang and Douglas, 1998;Knowlton, 2001;Muller-Parker and Davy, 2001;Baumgarten et al, 2015;Rädecker et al, 2015;Röthig et al, 2016;Tilstra et al, 2019;Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%